A probabilistic model for waiting time in achieving family planning goals - Singh, Tanya; Singh, Brijesh P.; Singh, Alok Kumar (Brazilian Journal of Biometrics, 2026)
The family decision process is a complex phenomenon. At some point, a couple may decide to interfere with the childbirth process in some way. The result of this decision is a sudden event that limits family size and gender composition. An important consideration in a study dealing with the number of children families wish to have is whether these desires include preference as to the child’s sex. The purpose of this paper is to propose five hypothetical rules that reflect the current preferences of parents regarding the size and gender composition of their children. Various combinations of marital durations, levels of fecundity, and rest periods (gestational period plus amenorrhea period) have been used to calculate the expected waiting time for each case to reach the desired family size. Additionally, for each case, an estimate of the truncation bias has been obtained. The lower limit of the range in each case is constructed by that value of the expected waiting time which corresponds to the pair of parameters andh = 0.92 years. The upper limit is the value of the expected waiting time derived by assuming and h = 1.25 years for an infinite duration of the marriage. As a result of this information, couples may be able to plan their families in such a way that all their financial and social obligations have been met by the time they plan to retire, which means that it will help make decisions about family planning at the micro level.